2018
DOI: 10.1111/nyas.13609
|View full text |Cite
|
Sign up to set email alerts
|

From intuition to intervention: developing an intonation‐based treatment for autism

Abstract: Autism affects ∼1.5% of children under age 8; its core symptoms include impairment in social-communicative functioning and repetitive behaviors/restricted interests. Music-based interventions have been considered one modality through which to treat autism. This report discusses considerations to take into account when developing a music-based intervention for a core symptom of autism. Treatment modality must be matched to symptom both clinically and theoretically, the behavior to be treated must be carefully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…The multisensory nature of musical activities and music's ability to induce emotions and regulate mood can increase patients’ engagement, motivation, and well‐being when used during the rehabilitation process 22–24 . Moreover, musical activities are widely available and can be adjusted to different levels of cognitive and motor function, as evidenced by several studies conducted on stroke, Parkinson's and Alzheimer's disease, traumatic brain injury, or autism 25–36 . They can also be adapted to the individual's ability and to the different recovery stages, ranging from more passive modalities, such as music listening, to active and highly demanding activities, such as reading or playing music.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multisensory nature of musical activities and music's ability to induce emotions and regulate mood can increase patients’ engagement, motivation, and well‐being when used during the rehabilitation process 22–24 . Moreover, musical activities are widely available and can be adjusted to different levels of cognitive and motor function, as evidenced by several studies conducted on stroke, Parkinson's and Alzheimer's disease, traumatic brain injury, or autism 25–36 . They can also be adapted to the individual's ability and to the different recovery stages, ranging from more passive modalities, such as music listening, to active and highly demanding activities, such as reading or playing music.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 , 24 Moreover, musical activities are widely available and can be adjusted to different levels of cognitive and motor function, as evidenced by several studies conducted on stroke, Parkinson's and Alzheimer's disease, traumatic brain injury, or autism. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 They can also be adapted to the individual's ability and to the different recovery stages, ranging from more passive modalities, such as music listening, to active and highly demanding activities, such as reading or playing music. Music‐based rehabilitation can be applied in rehabilitation settings, but there are also home‐based interventions that include self‐administered sessions with or without the assistance of a caregiver that may be excellent to maintain and enhance functioning in chronic stages.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen (21%) measured phonetic inventory either in imitation or from a spontaneous speech sample (Biller et al, 2022; Broome et al, 2021; Chenausky et al, 2016, 2018, 2021; Chenausky, Nelson, & Tager‐Flusberg, 2017; Chenausky, Norton, et al, 2022; Chenausky, Norton, & Schlaug, 2017; Chenausky & Schlaug, 2018; Kim & Seung, 2015; Landa et al, 2013; Petinou, 2021; Schoen et al, 2011; Yoder et al, 2015), 11 (17%) examined speech rate or diadochokinetic rate (DDK; rapidly produced sequences of syllables) (Chenausky et al, 2019, 2020, 2021; Deshmukh, 2012; Mahler, 2012; Mandelbaum et al, 2006; Nadig & Shaw, 2011; Patel et al, 2020; Shriberg et al, 2001, 2011; Velleman et al, 2010), seven (11%) examined the consistency or stability of speech production (Chenausky et al, 2019, 2020, 2021; Deshmukh, 2012; Gladfelter & Goffman, 2018; Mahler, 2012; Shriberg et al, 2011), six (9%) examined motor‐related feeding/eating behaviors (Amato & Slavin, 1998; Brisson et al, 2012; McDaniel et al, 2018; Peterson et al, 2016, 2019; Yoder et al, 2015), five (8%) examined speech intelligibility (Gabig, 2008; Koegel et al, 1998; Lyakso et al, 2017; Petinou, 2021; Shriberg et al, 2001), five (8%) examined vocalization quality (Chenausky, Nelson, & Tager‐Flusberg, 2017; Plumb & Wetherby, 2013; Schoen et al, 2011; Sheinkopf et al, 2000; Trembath et al, 2019), four (6%) examined resonance quality (Chenausky et al, 2019, 2020, 2021; Shriberg et al, 2011), and th...…”
Section: Resultsmentioning
confidence: 99%
“…It is unsurprising to find smaller effect sizes in an RCT than in case-control formats, just as it is common to find smaller effect sizes in a case-control study than a proof-of-concept study. 35 There can be many factors that give rise to this effect, such as a bias for selecting "model participants" in the early stages of an intervention, regression to the mean over repeated samples of the same population, or simple within-population variation. In our RCT, we observed that the participants seemed more severely affected than those from the case-control stage of the study.…”
Section: Discussionmentioning
confidence: 99%